Prevalence and associated factors of fatigue among breast cancer patients in Malaysia—A prospective study - Fares M. S. Muthanna, Muhammad Shahid Iqbal, Mahmathi Karuppannan, Egbal Abdulrahman, Najmee Adulyarat, Mokhtar AbdHafiz AbdAlhamid Al-Ghorafi, Humam Shaaban Barhoum (Journal of Applied Pharmaceutical Science, 2022)
The aim of this study was to determine the prevalence and factors associated with fatigue among breast cancer patients in Malaysia. This study was a prospective observational study and data were collected from medical records of Hospital Kuala Lumpur, University of Malaya Medical Center, and National Cancer Institute in the period between July 2019 and April 2020. The incidence of fatigue was determined by detecting whether or not fatigue developed during the course of chemotherapy. Severity of fatigue was determined by the Brief Fatigue Inventory scale after informed written consent was obtained. A chi-squared test was used to analyze the correlations between categorical variables, and logistic regression was used to evaluate the associations of risk factors with the presence of cancerrelated fatigue. Out of a total population of 576 breast cancer patients, 292 had met the inclusion criteria and fatigue occurred at a rate of 58.9%. Our findings indicated that age, body mass index, smoking, number of chemotherapy regimens, fluorouracil, epirubicin, and cyclophosphamide were all associated with the presence of fatigue among breast patients (p < 0.05). This study finds that the prevalence of fatigue in breast cancer patients was high and suggests that effective management of both demographic and clinical factors may reduce fatigue severity and improve the overall health status of cancer patients.
Keywords: Cancer-related fatigue, prevalence, associated factors, breast cancer